Breeding and genetic approaches to the estimation of quality prospects of winter durum wheat hybrids - N. E. Samofalova; M. A. Avramenko; A. P. Samofalov; N. P. Ilichkina (Зерновое хозяйство России)
One of the main requirements for the quality of winter durum wheat grain is the development of varieties with tough elastic gluten. The breeding process in this direction will be more successful if the assessment of the trait is known at the early stages. In our study SDS-sedimentation was used for such an assessment. In addition to assessing the quantitative severity of the SDS-sediment index, the breeder should be aware of the efficiency of high-quality progeny selection in generations of hybrids, the prospects of the population, the breeding value of the initial components involved in hybridization. In this regard, the main purpose of the conducted research is to reveal the efficiency of selection for the gluten quality from SDS-sedimentation in hybrid populations (F2 – F4) of winter durum wheat using breeding and genetic parameters. There have been presented the study results of 14 hybrid combinations of winter durum wheat obtained from crossing of the varieties with different or equal amount of sediment. It was shown that the response of hybrid populations (F2 – F4 ) to the selection of high-qualitative genotypes with different intensities was ambiguous, and in most combinations it was low or absent. The realized heritability in the groups of selection greatly varied depending on the severity of the selection; on the parental forms taken for hybridization; on the environmental conditions during the grain formation and ripening. There were identified such promising hybrid populations as “Kremona” × “Kurant”, “Terra” × “Kremona”, “Kremona” × “Terra”, “Zolotko” × “Aksinit”, “Zolotko” × “Kremona” in which the genotypic shift and realized heritability are revealed in all generations and selective groups.